Youth as Architects of Social Change Global Efforts to Advance Youth-Driven Innovation - Bastien, Sheri; Holmarsdottir, Halla B. (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
XXIV, 353 p. 14 illus., 10 illus. in color.